Shenandoah : a story of conservation and betrayal - Eisenfeld, Sue (University of Nebraska Press, 2014)
For fifteen years Sue Eisenfeld hiked in Shenandoah National Park in the Virginia Blue Ridge Mountains, unaware of the tragic history behind the creation of the park. In this travel narrative, she tells the story of her on-the-ground discovery of the relics and memories a few thousand mountain residents left behind when the government used eminent domain to kick the people off their land to create the park. With historic maps and notes from hikers who explored before her, Eisenfeld and her husband hike, backpack, and bushwhack the hills and the hollows of this beloved but misbegotten place.